The Problem of Method in Theology - Helmut Jan Sobeczko (Wrocławski Przegląd Teologiczny)
The problem of method (methods) in theology is connected to the understanding of theology as a science as well as to the understanding of its identity. In theology understood as a science there is no single scientific method, because there are many theological disciplines and each of them uses its own methods. Therefore, we speak in fact of the pluralism of the theological methods. In this paper the Author limited the analysis of the methodological issues of theological studies to showing the basic methodological elements: first, to those which are common to all theological disciplines and second, he presented one of the most important hermeneutic methods, i.e. the linguistic one, which is a method of analysing texts, used mainly in biblical, liturgical and patristic sciences. In the last part of the paper he refers to some of the newest works concerning the methods used in different theological disciplines.